Michel Temer e a persuasão no discurso de posse presidencial: um olhar sistêmico-funcional - Milanez, Aline Andrea Zamboni (2019)
The ability to employ argumentation belongs to the family of human actions that seek to persuade, presenting itself as an alternative to the use of physical violence, therefor, since it allows one to resort to manipulation, which represents a discursive social practice of dominant groups equipped for the maintenance of power. The objective of this master’s dissertation is the critical analysis of the rhetorical devices in Michel Temer's speech on the occasion of his investiture as president of the nation, focusing on how persuasion is woven throughout the inauguration discourse. Michel Temer took office on May 12, 2016, following the impeachment of president Dilma Rousseff. The general strategies of a persuasive discourse are largely semantic-pragmatic, and, as in the case of the implementation of ideologies, these meanings can be (de)emphasized by the (de)topicalization of meanings by specific speech acts, by local meanings that may be more or less precise, by the manipulation of explicit versus implicit information, by means of lexicalization, metaphors and other rhetorical figures. One of the elements of communication that assumes a fundamental part in the manipulation of opinions is the notion of evaluation, called “appraisal” by Systemic-Functional Linguistics, and that, in summary, expresses the opinion of the speaker about the parameters on the definition of “good” and “bad”. Appraisal embraces the notion of “attitude token” - the implicit assessment - to denote the way in which ideational meaning can be "saturated" in evaluative, that is, intrapersonal terms. The research intends to answer the following questions: (a) What resources does persuasion use in Michel Temer's inauguration speech? (b) What is the role of appraisal in this process? This research shows that implicit persuasion occurs in the underlying text and that, for its revelation, it is necessary to focus on the relation between the lexical choices made in the microstructure of the text and the values which are found in the macrostructure of the discourse, whose understanding depend largely on the interlocutor's frame